Dynamic microbial changes in exacerbation of chronic obstructive pulmonary disease - Choi, Yong Jun; Park, Hye Jung; Kim, Chi Young; Choi, Aeri; Cho, Jae Hwa; Byun, Min Kwang (Frontiers in Microbiology, 2024)
BackgroundMicrobial profiles in patients with chronic obstructive pulmonary disease (COPD) provide insights for predicting, preventing, and treating exacerbations. This study aimed to analyze the impact of microbial diversity and spectrum on COPD exacerbation.MethodsFrom November 1, 2018, to May 31, 2023, we prospectively enrolled patients with stable disease (SD) and exacerbation of COPD (ECOPD). Sputum samples were collected for microbiome DNA sequencing, and amplicon sequence variants were analyzed.ResultsWe collected sputum samples from 38 patients: 17 samples from patients with SD and samples from patients with ECOPD at two time points—during exacerbation (AE-1: 21 samples) and again during stabilization after 2 weeks of treatment (AE-2: 17 samples). Alpha diversity indices, specifically observed feature count and Fisher’s alpha index, were significantly higher in SD (133.0 [98.0–145.0]; 17.1 [12.7–19.6]) compared to AE-1 (88.0 [72.0–125.0], p = 0.025; 10.9 [8.5–16.1], p = 0.031). The SD showed significantly higher abundances of Neisseria (linear discriminant analysis [LDA] 4.996, adj.p = 0.021), Fusobacterium (LDA 3.688, adj.p = 0.047), and Peptostreptococcus (LDA 3.379, adj.p = 0.039) at the genus level compared to AE-1. At the species level, N. perflava (LDA 5.074, adj.p = 0.010) and H. parainfluenzae (LDA 4.467, adj. p = 0.011) were more abundant in SD. Hub genera in the microbial network included Haemophilus, Granulicatella, Neisseria, Lactobacillus, and Butyrivibrio in SD and Streptococcus, Gemella, Actinomyces, Klebsiella, and Staphylococcus in AE-1.ConclusionCOPD exacerbations are linked to changes in specific strains of normal flora. Maintaining microbial diversity and balance within the microbial network is critical for preventing and managing COPD exacerbations.